2021
DOI: 10.1016/j.pmedr.2021.101451
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the COVID-19 pandemic: Contemplative practice behaviors are associated with better mental health outcomes and compliance with shelter-in-place orders in a prospective cohort study

Abstract: Psychosocial health can influence the development and experience of several chronic diseases, and has been negatively affected for many individuals amid the COVID-19 global pandemic. To understand the impact of contemplative practices on emotional and mental health during COVID-19, the Stanford WELL for Life Study (US component), incorporated a series of additional surveys into its ongoing study. A total of 1,097 participants residing in California who responded to at least one of three COVID-19 surveys were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…Twenty-two studies were conducted in China ( 27 , 31 34 , 37 , 39 , 40 , 44 , 47 , 55 , 62 65 , 67 , 69 73 , 75 77 ), six in Saudi Arabia ( 18 , 21 23 , 25 , 26 ), five in India ( 10 , 41 , 46 , 60 , 61 ), three in the United States ( 35 , 42 , 45 ) and three in Turkey ( 38 , 49 , 66 ), and these were the most frequent countries included in this review. Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-two studies were conducted in China ( 27 , 31 34 , 37 , 39 , 40 , 44 , 47 , 55 , 62 65 , 67 , 69 73 , 75 77 ), six in Saudi Arabia ( 18 , 21 23 , 25 , 26 ), five in India ( 10 , 41 , 46 , 60 , 61 ), three in the United States ( 35 , 42 , 45 ) and three in Turkey ( 38 , 49 , 66 ), and these were the most frequent countries included in this review. Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , 40 , 44 , 47 , 55 , 63 65 , 67 , 69 73 , 75 77 ), functional food (supplements) or herbs ( n = 20) ( 17 24 , 29 , 36 , 38 , 43 , 49 52 , 57 59 ), mind-body practice or spiritual practice ( n = 9) ( 28 , 35 , 42 , 45 , 48 , 54 , 60 , 61 , 74 ), Ayurveda ( n = 2) ( 10 , 41 ), homeopathy ( n = 1) ( ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [63] observed that contemplative practice behaviors are associated with lockdown compliance. More generally, cognitive attitudes seem to be a strong predictor of compliance, according to [64].…”
Section: Previous Evidence Collected During the Covid-19 Crisismentioning
confidence: 99%